Using Powerpoint Slide Media to Improve Student Learning Outcomes in Learning Mathematics in Primary School Class IV - Hery Kresnadi (Universitas Tanjungpura, 2018)
The purpose of this research, in general, is to describe the improvement of student learning outcomes using powerpoint slide media on learning mixed calculation operations in class IV State Elementary School 18 Sungai Kakap The method used is descriptive method with Class Action Research form. This research was conducted in 3 cycles and got an idea of how the design of learning, the implementation of learning, the characteristics of slide powerpoint media, the technical implementation of learning evaluation and improvement of student learning outcomes. There is an increase in learning outcomes in each cycle, from 37% of students who reach KKM in cycle 1 to 68% in cycle 3.